Endoscopic ultrasound-guided gallbladder drainage reduces adverse events compared with percutaneous cholecystostomy in patients who are unfit for cholecystectomy - Teoh, Anthony Yuen Bun; Serna, Carlos; Penas, Irene; Chong, Charing Ching Ning; Perez-Miranda, Manuel; Ng, Enders K. W.; Lau, James Yun Wong (Endoscopy, 2017)
Background and study aim There are no data comparing endoscopic ultrasound (EUS)-guided gallbladder drainage (EGBD) with percutaneous cholecystostomy as a treatment for patients with acute cholecystitis.Patients and methods This was a 1 : 1 matched cohort study of all patients who were unfit for cholecystectomy and underwent EGBD or percutaneous cholecystostomy instead for the treatment of acute cholecystitis. The outcomes were matched for age, sex, and American Society of Anesthesiologists grade. Outcome measures included the technical and clinical success rates, adverse events, hospital stay, the number of unplanned admissions, and mortality.Results Between November 2011 and August 2014, a total of 118 patients were included in the study (59 EGBD, 59 percutaneous cholecystostomy). Technical and clinical success rates were similar. In the EGBD group, significantly fewer patients suffered from overall adverse events (19 [32.2 %] vs. 44 [74.6 %]; P < 0.001) and serious adverse events (14 [23.7 %] vs. 44 [74.6 %]; P < 0.001) compared to the percutaneous cholecystostomy group. Patients in the EGBD group required fewer unplanned admissions (4 [6.8 %] vs. 42 [71.2 %]; P < 0.001), which were due to problems related to the cholecystostomy tube in 95.2 %. The 30-day adverse event rates were similar between the groups (17 [28.8 %] vs. 10 [16.9 %]; P = 0.13). For instance, recurrent acute cholecystitis occurred in 0 patients in the EGBD group and in 4 (6.8 %) patients in the percutaneous cholecystostomy group (P = 0.12). The 30-day mortality rates were non-significantly higher in the EGBD group (5 [8.5 %] vs. 1 [1.7 %]; P = 0.21).Conclusions EGBD and percutaneous cholecystostomy were both effective means of achieving gallbladder drainage. EGBD may be a promising alternative to percutaneous cholecystostomy for treatment of acute cholecystitis in patients who are unfit for surgery, provided that experienced endosonographers are available.